2011
DOI: 10.2514/1.50543
|View full text |Cite
|
Sign up to set email alerts
|

Substitution of Hot-Gas Lateral Jets by Cold-Gas Jets in Supersonic Flows

Abstract: The supersonic flow around a rocket piloted by thrusters has been investigated. Steady Reynolds-averaged Navier-Stokes computations and pressure measurements in a wind tunnel, using pressure taps and pressuresensitive paint, have been performed. For experimental investigations, real hot-gas thrusters have been replaced by cold-gas jets using a lower total pressure and a different gas. The uniqueness of this work involved calibrating those cold-gas thrusters in order to reproduce an aerodynamic interference ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Some data for the DLR model were obtained for a hot-gas jet [11], for which the model diameter was 70 mm but the jet nozzle diameter remained 4 mm. More recent results from some of the same authors included additional results from wind-tunnel investigations on hot-gas lateral jet ejection [14,15] and substitution of hot-gas lateral jets by cold-gas simulants in supersonic flow [16].…”
Section: Introductionmentioning
confidence: 98%
“…Some data for the DLR model were obtained for a hot-gas jet [11], for which the model diameter was 70 mm but the jet nozzle diameter remained 4 mm. More recent results from some of the same authors included additional results from wind-tunnel investigations on hot-gas lateral jet ejection [14,15] and substitution of hot-gas lateral jets by cold-gas simulants in supersonic flow [16].…”
Section: Introductionmentioning
confidence: 98%
“…More recent results from these authors include additional results from wind tunnel investigations on hot-gas lateral jet ejection 11,12 and an experimental and computational study on the substitution of hot-gas lateral jets by cold-gas simulants in supersonic flow. 13 Hold et al 14 performed a computational investigation based on the experimental data of Stahl et al, 11 finding that it was necessary to use a realgas, nonreacting, multispecies-based solution to most accurately predict the missile surface pressures due to the JI. However, Hold et al 14 also found that an ideal-gas hot-air jet provided reasonable aerodynamic force and moment predictions compared with the multispecies hot-gas predictions.…”
Section: Introductionmentioning
confidence: 99%
“…The understanding of the phenomena that occur with respect to the reaction control of missiles has matured [1,2]. But it is still difficult to predict precisely the aerodynamic jet interferences in order to evaluate jet thruster effectiveness, because of the difficulties in achieving similitude between a wind tunnel test and actual flight conditions [3][4][5]. With the advances in CFD technology and high performance computing, the CFD technique has come to play an important part in predicting jet interferences of lateral jets [5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%